2015
DOI: 10.1007/s10577-014-9448-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific recombination maps for individual macrochromosomes in the Japanese quail (Coturnix japonica)

Abstract: Meiotic recombination in the Japanese quail was directly studied by immunolocalization of mutL homolog 1 (MLH1), a mismatch repair protein of mature recombination nodules. In total, 15,862 crossovers were scored along the autosomal synaptonemal complexes in 308 meiotic nuclei from males and females. Crossover frequencies calculated from MLH1 foci show wide similitude between males and females with slightly higher number of foci in females. From this analysis, we predict that the sex-averaged map length of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 69 publications
2
12
0
Order By: Relevance
“…In most cases, metacentric/submetacentric chromosomes show higher amounts of recombination at telomeric regions, a deficiency around the centromere (within 1 μm or less), and a bimodal or a multimodal distribution along the chromosome arms. In contrast, the acrocentric bivalents have pronounced recombination peaks close to the proximal region and the telomere of the long arm [Rahn and Solari, 1986;Pigozzi and Solari, 1999a, b;del Priore and Pigozzi, 2015;Pigozzi and del Priore, 2016]. These observations support the notion that 132 the primary chromosome structure plays a role in the distribution of crossing over at a coarser level.…”
Section: Crossover Markers Along Avian Scsmentioning
confidence: 54%
See 1 more Smart Citation
“…In most cases, metacentric/submetacentric chromosomes show higher amounts of recombination at telomeric regions, a deficiency around the centromere (within 1 μm or less), and a bimodal or a multimodal distribution along the chromosome arms. In contrast, the acrocentric bivalents have pronounced recombination peaks close to the proximal region and the telomere of the long arm [Rahn and Solari, 1986;Pigozzi and Solari, 1999a, b;del Priore and Pigozzi, 2015;Pigozzi and del Priore, 2016]. These observations support the notion that 132 the primary chromosome structure plays a role in the distribution of crossing over at a coarser level.…”
Section: Crossover Markers Along Avian Scsmentioning
confidence: 54%
“…The presence of 2 classes of COs in birds has not yet been tested, but both RNs and MLH1 foci show CO interference in birds [Pigozzi and Solari, 1997;Pigozzi, 2001]. In addition, comparison of the number of MLH1 foci and chiasmata in oocytes of the same species favors the view that MLH1 foci account for most recombination events in birds [Rodionov et al, 1992;Pigozzi, 2001;Rodionov and Chechik, 2002;del Priore and Pigozzi, 2015].…”
Section: Crossover Markers Along Avian Scsmentioning
confidence: 99%
“…In the anoles, the distribution is extremely uneven and is characterized by strong distal peaks, with more than 90% of the crossovers occurring at the distal 10% of the chromosome arm lengths [Lisachov et al, 2017]; in contrast, in the agama, the distribution is more even. With a high SC length and a large number and more even distribution of MLH1 foci, the steppe agama more resembles birds than anoles [del Priore and Pigozzi, 2015]. The degree of crossover interference in T. sanguinolentus is moderate and is similar to that measured in the anoles.…”
Section: Male Meiotic Recombination In the Steppe Agamamentioning
confidence: 66%
“…Recombination in reptiles has been predominantly studied by determining chiasma count and positions at meiotic metaphase I chromosomes [Reed et al, 1992;Hall, 2009;Lamborot et al, 2012]. Immunolocalization of the mismatch-repair protein MLH1 (mutL homolog 1), which marks mature recombination nodules in meiosis along the SCs, provides much more detailed and precise estimates of crossover frequency and distribution in vertebrates [Moens, 2006;del Priore and Pigozzi, 2015;Lisachov et al, 2017;Ruiz-Herrera et al, 2017].…”
mentioning
confidence: 99%
“…In birds, cytogenetic studies revealed the presence of multiple CO events along the largest macrobivalents in the chicken, the preferential location of recombination events toward the ends of chromosomes in zebra finches and the limited variation in recombination rates between sexes in pigeons and quails [ 8 10 ]. Genetic linkage analysis in chickens showed that recombination rates were unusually high in this species, especially when compared to recombination rates in mammals [ 11 13 ].…”
Section: Introductionmentioning
confidence: 99%